Restoring civil societies : the psychology of intervention and engagement following crisis - Jonas, Kai J.; Morton, Thomas A. (Social issues and interventions., 2012)
"Restoring Civil Societies examines the role of civic engagement as a form of prosocial behavior motivated by a commitment to higher-order norms. Civic engagement--from bystander intervention to organizing collective activity--is distinguished as a collective effort by which individuals re-institute the civil basis of society in the wake of a social rupture, whether from war, natural disaster, or other causes. Restoring Civil Societies fills the gap between basic research on social issues and the translation into social policy or program interventions"--